Equidosimetry Ecological Standardization and Equidosimetry for Radioecology and Environmental Ecology - Bréchignac, F.; Desmet, G. (Nato Security through Science Series C, Environmental Security, 2005)
Considerable experience with radioecological and related ecological research on terrestrial and aquatic ecosystems has been achieved, especially after the Chernobyl accident. The combined effects of the radiation, chemical and biological factors, after a contamination of the environment and during its remediation have shown an interactive complexity that highlights the need for equidosimetrical evaluations of the influence of the various stressors and the need for their ecological normalization. In radioecology and radiation protection, methods of radiation dosimetry are key for dose assessment. It is therefore highly desirable to develop a clear theoretical approach as well as a practical method of equidosimetry that would allow for an ecological normalization of the different stressors in unified uniform units, especially for comparison purposes.